Exploring the biological basis of acupuncture treatment for traumatic brain injury: a review of evidence from animal models - Wu, Minmin; Song, Wenjing; Teng, Lili; Li, Jinting; Liu, Jiayu; Ma, Hanwen; Zhang, Ge; Zhang, Jiongliang; Chen, Qiuxin (Frontiers in Cellular Neuroscience, 2024)
Traumatic brain injury (TBI) occurs when external physical forces impact the brain, potentially causing long-term issues such as post-traumatic stress disorders and cognitive and physical dysfunctions. The diverse nature of TBI pathology and treatment has led to a rapid acceleration in research on its biological mechanisms over the past decade. This surge presents challenges in assessing, managing, and predicting outcomes for TBI cases. Despite the development and testing of various therapeutic strategies aimed at mitigating neurological decline after TBI, a definitive cure for these conditions remains elusive. Recently, a growing focus has been on preclinical research investigating acupuncture as a potential treatment method for TBI sequelae. Acupuncture, being a cost-effective non-pharmacological therapy, has demonstrated promise in improving functional outcomes after brain injury. However, the precise mechanisms underlying the anticipated improvements induced by acupuncture remain poorly understood. In this study, we examined current evidence from animal studies regarding acupuncture’s efficacy in improving functional outcomes post-TBI. We also proposed potential biological mechanisms, such as glial cells (microglia astrocytes), autophagy, and apoptosis. This information will deepen our understanding of the underlying mechanisms through which acupuncture exerts its most beneficial effects post-TBI, assisting in forming new clinical strategies to maximize benefits for these patients.